Strategi Pengelolaan Pariwisata Halal Kota Surabaya - Ahyak Fiqih (Maliyah : Jurnal Hukum Bisnis Islam, 2019)
Professional management of management by Coordinating with the tourism office, promoting scientific activities as the cultivation of religious values, and fostering human resources (HR) to all Nadzirs. Management strategies in the traditional tourism sector by offering alternatives such as religious tourism, culinary delights, and traditional markets. 2) Inhibiting factors: Human resource awareness from both tourists and Nadzirs, inadequate facilities related to visitors' quantity. 3) Supporting factors: Islamic environment such as separation of places for male and female tourists, preparation of facilities such as electricity, water, lodging, places for ablution, toilets, and mosques. Suggestion: Conduct training related to the development of halal tourist attractions, provide directions to all tourists both online and offline, expand tourist areas by acquiring surrounding land, rejuvenating and repairing areas, and reforestation.